Evaluating the Biocompatibility of Maxillofacial Silicone Enhanced by Hexagonal Boron Nitride Particles - Ali, Montather Salam; Abdul-Ameer, Faiza Mohammed (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This study aims to evaluate the biocompatibility of a novel filler material intended to improve the longevity of polymer systems used in prosthetics in respect of cytotoxicity and skin irritation. RTV50F silicone elastomer incorporated with various percentages of hexagonal boron nitride (H-BN) (0.1, 0.3, 0.5, 0.7, and 1 wt%) have been tested. Silicone without H-BN was utilized as the control for comparison. The in vitro cytotoxicity test includes specimens (n=18) with 10 mm in diameter and 2 mm in thickness applied directly to the normal human fibroblast cell line (NHF) and incubated for 72 hours, then 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to determine the cell viability. The skin irritation test was conducted in vivo, in which specimens (n=12) with 25 mm × 25 mm dimensions were applied on the back of 5 different rabbits for 4 hours, then the skin response was evaluated after 24, 48, and 72 hours. The acquired in vitro data were statically analyzed using one-way ANOVA and post-hoc Tukey’s tests with GraphPad Prism 8, where P-value < 0.05 was considered statistically significant. The H-BN powder and silicone specimens were studied via field emission scanning electron microscopy (FE-SEM). The results revealed a negligible effect of maxillofacial silicone on cell viability after 72 hours of incubation, only one group (1wt%) showed a significant difference compared to the control group but the toxicity percentage didn’t exceed 30% of cell viability and there was no skin irritation during the in vivo test.